In Search of a National Identity – Performances of Englishness in Popular Culture (KULT_online, 2011)
Simon Featherstone's book investigates performances of national identity that have constructed a distinctively English identity in the 20th century. The strength of the publication lies in its selection of characteristic instances from popular culture that are presented in a concise, witty, and accessible way. Emphasising concepts and seemingly trivial instances that, in many other publications on the subject, are neglected or simply presupposed, Featherstone's book makes a valuable contribution to the interdisciplinary field of study on Englishness.